2017
DOI: 10.1021/acs.chemmater.7b00070
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure Evolution and Modes of Charge Storage in Secondary Li–FeS2 Cells

Abstract: In the pursuit of high-capacity electrochemical energy storage, a promising domain of research involves conversion reaction schemes, wherein electrode materials are fully transformed during charge and discharge. There are, however, numerous difficulties in realizing theoretical capacity and high rate capability in many conversion schemes. Here we employ operando studies to understand the conversion material FeS 2 , focusing on the local structure evolution of this relatively reversible material. X-ray absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 63 publications
8
78
0
Order By: Relevance
“…The SAED pattern of lithiated FeS 2 in Figure 1I shows broad rings that arise due to diffraction from Li 2 S, but no diffraction spots from body-centered cubic Fe were detected. A recent study used X-ray diffraction and pair distribution function analysis to conclude that the small Fe clusters produced through this electrochemical conversion reaction are in fact disordered, 35 which aligns with our observations. High-resolution imaging of the reacted material revealed Li 2 S lattice fringes and Fe particles embedded within this Li 2 S matrix (Figure S1).…”
Section: àsupporting
confidence: 89%
“…The SAED pattern of lithiated FeS 2 in Figure 1I shows broad rings that arise due to diffraction from Li 2 S, but no diffraction spots from body-centered cubic Fe were detected. A recent study used X-ray diffraction and pair distribution function analysis to conclude that the small Fe clusters produced through this electrochemical conversion reaction are in fact disordered, 35 which aligns with our observations. High-resolution imaging of the reacted material revealed Li 2 S lattice fringes and Fe particles embedded within this Li 2 S matrix (Figure S1).…”
Section: àsupporting
confidence: 89%
“…[30][31][32] Further studying the poly-sulfides such as TiS4 and VS4, mainly for their conversion-type mechanism leading to large capacities at low potential, researchers have noted that such compounds were also enlisting sulfur redox activity. [33][34][35][36][37] Similarly, by reinvestigating the crystalline LiMS2 (M = Ti, V, Cr, Fe) layered sulfides directly prepared from solid-state reactions, scientists also found that in some of these phases, both Li removal and insertion are possible, but it remains unclear whether the process involves anionic besides cationic redox activity. [38][39][40] Thus, deciphering the sulfur redox process in such compounds could be of paramount importance to further understand the oxygen redox in Li-rich layered oxides.…”
Section: Introductionmentioning
confidence: 99%
“…(2)], FeS 2 was actively researched for high‐temperature batteries with molten salt electrolytes in the 1980–1990s, and commercialized by Energizer as primary Li/FeS 2 cells . It has gained a renewed interest in the latter years, as more research in the area of batteries turned to conversion‐type electrodes …”
Section: Polysulfide Materials As Electrodes In Libsmentioning
confidence: 99%
“…However, the subsequent cycling proceeds through more complex mechanisms, and in most accounts, the parent pyrite phase FeS 2 is not recovered . In fact, the reported mechanisms for charge/discharge processes beyond the unique first cycle are often controversial and depend strongly on cycling conditions, such as temperature, rate, and electrolyte . Nevertheless, there is no doubt about the important role of the anion redox chemistry in the performance of FeS 2 electrodes, as their cycling features the breakage‐recombination of the disulfide (S−S) 2− bonds.…”
Section: Polysulfide Materials As Electrodes In Libsmentioning
confidence: 99%